Traslation of health research evidence into policy and planning in Nepal: an appraisal 2016. (2016)
SUMMARY: Background: Knowledge derived from research may be of little value unless it is put into practice. Although a large number of studies have been carried in different health related issues in Nepal, the use of evidences from such studies in policy making process has not been fully explored. Therefore, this study was undertaken to assess the country level efforts to link research to action in the present scenario and to develop appropriate mechanisms to strengthen assessing, appraising and translating evidence for policy makers. Method: It was a qualitative study based on key informant interview of policy makers and researchers. The Ethical Review Board of Nepal Health Research Council (NHRC) granted the ethical approval for this research. Twenty-five researchers and twelve policy makers were sampled using the theory of saturation. All the interview were audio recorded, transcribed in participants original language (Nepali), translated to English, coded line by line and then developed into themes. Data were analyzed manually using thematic analysis technique. A training workshop on critical appraisal of evidence and protocol development on systematic review and meta-analysis was organized to enhance the competency of health researchers in the field and ultimately help policy makers on evidence based decision making in Nepal after the completion of research project as most of the research participants highlighted the need of capacity development for evidence synthesis. Results: Research participants were involved in a diverse type of research, including research designed to improve program effectiveness, feasibility study of communitybased interventions, entomological, epidemiological and serological study on disease like Visceral leishmaniasis (Kala-azar), national health survey and interventional study. The number of health research in past decades was reported to be in increasing trend with increasing resources. However, quality of those researches was not up to the standard. Generation of new information, addressing some practical challenges, forming a base for policy or guideline and catering the interest of donors in a particular field were cited as main reason for conducting research. Contradictory opinions were put forward regarding the base of health-related policies. Most of the researchers opined that national and international research findings create the base for drafting policy while other depicted the prominent role of politicians presenting them as the ultimate decision makers. Policy makers identified stakeholders/experts consultation as measures to pull evidence when needed. Researchers seem to have considered dissemination in workshops, presentation in conferences and publication in scientific journals as measures to push their findings to policy making level. Participants identified conducting of a workshop as the most common exchange effort. Participants shared their realization of the need for evidence synthesis, which could facilitate policy makers to find all relevant quality assured research findings in single document. According to the participant, it could take the form of meta-analysis, systematic review or simply the synopsis of main result of research in the form of a fact sheet or annual abstract book. Instability in the leadership, limited opportunity for interaction between researchers and policy makers and poor research reading culture of decision makers were highlighted as key challenges in linking health research to the policy. Close group media interaction, communication/dissemination of research findings in the presence of local leaders in districts and regions, orientation to the Member of Parliament on health-related indicators, updating political leaders on latest research findings were suggested as options for utmost utilization of health research findings. Conclusions: With increasing resources, a number of health researches seem to have increased covering diverse areas in the present time. Although the use of health research seems to be increasing, there are some challenges which if addressed could further improve evidence-informed decision-making in Nepal. Promotion of systematic review and meta-analysis of studies can contribute in promoting evidenced based health policy and plan formulation in Nepal.